2019
DOI: 10.1007/s42765-019-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Functional Fiber and Smart Textile

Abstract: The research and applications of fiber materials are directly related to the daily life of social populace and the development of relevant revolutionary manufacturing industry. However, the conventional fibers and fiber products can no longer meet the requirements of automation and intellectualization in modern society, as well as people's consumption needs in pursuit of smart, avant-grade, fashion and distinctiveness. The advanced fiber-shaped electronics with most desired designability and integration featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(93 citation statements)
references
References 134 publications
(149 reference statements)
0
90
0
Order By: Relevance
“…[14] Reports from several authors have indicated the following interesting achievements; drastic increase in the PCE from 3.8% in 2009, [15] to 23.7% in a period of 10 years, a remarkable improvement in stability from a few hours of operation to a maximum life time of 1 year [16] and beyond, broadened range of materials including flexible and cheap substances and a notable reduction in production costs due to the ease of assembling methods. [17] However, due to the numerous advantages associated with the fiber geometry such as the light weight, increased flexibility, and the ease of conversion into other structures such as fabrics, together with an increasing demand for textile-based energy-harvesting devices, developed with the intent of powering in body, on body, near body, and other wearable electronics, [18][19][20] the research in the domain of fiber-shaped solar cells is slowly following the footsteps of their 2D counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Reports from several authors have indicated the following interesting achievements; drastic increase in the PCE from 3.8% in 2009, [15] to 23.7% in a period of 10 years, a remarkable improvement in stability from a few hours of operation to a maximum life time of 1 year [16] and beyond, broadened range of materials including flexible and cheap substances and a notable reduction in production costs due to the ease of assembling methods. [17] However, due to the numerous advantages associated with the fiber geometry such as the light weight, increased flexibility, and the ease of conversion into other structures such as fabrics, together with an increasing demand for textile-based energy-harvesting devices, developed with the intent of powering in body, on body, near body, and other wearable electronics, [18][19][20] the research in the domain of fiber-shaped solar cells is slowly following the footsteps of their 2D counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable devices integrated smart-textiles and multifunctional suits are receiving significant research enthusiasm due to the urgent needs of constantly monitoring human body condition to prevent disease and provide extra protection, and other promising future applications such as body function enhancement [1][2][3]. Power supply for these integrated intelligent clothing remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous methods have been developed to improve the sensor performance by optimizing the nanomaterials, including carbon nanotubes (CNTs) [1], graphene nanosheets [9], metal nanowires [10][11][12][13][14][15][16][17][18][19], conductive polymers [20], and their composite materials [21][22][23][24][25][26]. Particularly, Ag nanowire (AgNW) has been widely explored as the sensing materials or conductive fillers in pressure sensors because of its excellent electrical properties.…”
Section: Introductionmentioning
confidence: 99%